Determinants of cervical cancer screening adherence in urban areas of Nakhon Ratchasima Province, Thailand - Sawitree Visanuyothin; Jiraporn Chompikul; Aroonsri Mongkolchati (Elsevier, 2015)
Summary: Cervical cancer is the most common disease among Thai women. The cervical cancer mortality rate has increased in the previous decade. Therefore, this cross-sectional study was conducted to examine the factors associated with cervical cancer screening adherence. Stratified sampling with the proportional to size method was used to select registered women aged 30-60 years. Of the 700 self-administered questionnaires distributed during July and September of 2012, 675 were returned, resulting in a response rate of 96.2%. Approximately 65.4% of the women were considered to be adherent to cervical cancer screening (i.e., maintainers) as defined by at least one screening within the recommended 5-year screening interval and the expectation of attending a screening in the future. Chi-square tests revealed that occupation, marital status, number of children, sexual activity, health insurance scheme, history of oral contraceptive pill use, perceived barriers, perceived benefits, and knowledge about cervical cancer prevention were significantly associated with cervical cancer screening adherence. After adjusting for occupation, marital status, number of children, and health insurance in the model, perceived barriers (Adj OR = 1.97, 95% CI = 1.24-3.10) and knowledge (Adj OR = 1.65, 95% CI = 1.13-2.41) remained significant predictors of cervical cancer screening adherence. These findings suggest that the non-housewives, women of single/separated/divorced/widowed status, and women with no children should be the first priorities for getting Pap tests. Strategies for overcoming the barriers of these women, such as using mobile units for cervical cancer screening, should be promoted. Education programs should be strengthened and promoted to overcome negative perceptions and knowledge deficiencies. Keywords: Cervical cancer, Screening, Adherence, Women's health